UPAYA HUKUM YANG DAPAT DIAJUKAN OLEH TERSANGKA JIKA DALAM PROSES PENYELIDIKAN DAN PENYIDIKAN POLRI TERDAPAT PELANGGARAN TERHADAP HAK – HAK TERSANGKA (STUDI PADA POLSEK UTARA SAMARINDA) - Tri Nurmisbah (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTSuspect dealing with the public prosecutor before the courts, both have the same status as well as the rights they have. Prosecutors will try to provide evidence to the court to convince a judge that the suspect guilty and deserve to get a penalty. Prosecutors will attempt to show the items of evidence relating to the unlawful acts alleged happened to the suspect. Even the public prosecutor can bring witnesses to incriminate a suspect. While the suspect himself is entitled to deny what has been alleged by wing evidence, even that which has been alleged is not true. Suspects could also bring witnesses to alleviate (a de charge witness). If the suspect was able to prove that he is innocent, then the interrogation of the suspect immediately stopped and the suspect is free from any claims that have been attributed to him. If the suspect can not prove that he is innocent, then the criminal proceedings against the suspect will be forwarded to the final stage. If there has been a violation of his rights by investigators, the suspect can do something that can make the investigator in question must be accountable for his actions. Legal remedies that may be filed by the suspect, his family and his lawyers are pre-trial efforts.With these pre-trial, the suspects could get justice for violations of their rights that have been carried out by investigators. Another thing that can be done by the suspects to investigators who have violated the rights of his to make efforts to force and violence against the suspect is to report the investigator to the authorities, that the investigators reported that have committed a crime by committing violence against suspects can be attributed to article 351 of the Criminal Code that resulted in the suspect suffered persecution both body and spirit. Obstacles encountered in providing legal protection against the suspect at the level of inquiries and investigations to find the material truth is not yet the enactment of existing laws and regulations as fully as there are sociological does not apply in the community. In addition due to the attitude of the defendant itself that can not be invited to cooperate. Another thing that causes the still incomplete enforcement of the rights of suspects because they rendahnyat ingkat professionalism of investigators and investigation authorities officials in performing their duties. Lack of facilities and infrastructure and the lack of funds to conduct investigations and examinations also cause is still somewhat difficult enforcement of g freely at will own investigators to conduct examination in the manner.